Aspectos tecnológicos dos rebanhos ovinos e caracterização epidemiológica da Língua Azul nos estados do Nordeste - Santos, Vanderlan Warlington Souza dos (2018)
The objective of this work was to determine the epidemiological situation of Bluetongue virus (VLA) infection in sheep herds and to characterize the technological and sanitary aspects in the states of Alagoas (AL), Ceara (CE), Maranhao (MA) , Paraiba (PB), Piaui (PI), Rio Grande do Norte (RN) and Sergipe (SE). For this purpose, 226 farms visited and applied a questionnaire where blood of 2.692 apparently healthy sheep collected. In the present study, a mean prevalence in the northeast of 60,62% (137/226) of positive animal properties and 26,52% (714/2.692) of seropositive sheep. A mean VLA seroprevalence of 33,06% (162/490) in sheep and 82,93% (34/41) in the herds, with at least one positive animal observed in the state of CE. In AL, a seroprevalence of 2,55% was observed (7/275) from the animals and 21.74% (5/23) on farms. In the MA State, 64,13% (177/276) of the animals and 100% (23/23) of the herds were positive. Regarding the RN State, of the 33 properties surveyed, 12 (36,36%) had seroreagents and 16 of the animals studied (4,04%) were positive. In PB State, 2,82% (8/284) of the sheep were seroreagent and of the 24 farms analyzed, 2 (8,33%) presented a positive animal. In the PI, 76,98% (291/378) of the animals and all the properties (32/32) were seroreagent. In SE State, 894% (53/593) of the sheep were positive and 58,0% (29/50) in the sampled herds showed positivity. There was a significant association (p <0,05) regarding the sex, age and degree of kinship of the animals. The acquisition of animals for replacement of the herds (p <0,05) (odds ratio = 5,87, 95% CI = 2,06-16,76, p = 0,001) was identified as a risk factor for BTV in the evaluated states. In this study, the technological and sanitary aspects verified that the breeding system most adopted in the Northeast was the extensive (84,07%), with the activity directed mainly to meat (84,07%). It was verified that the animals were handled in sheepfolds on 68,14% of the properties. The predominance of joint rearing with goats and cattle was too observed. It was verified that 81,42% of the properties had some kind of technical assistance and that only 31,86% of the owners invest in their professional qualification of the employees. The most adopted practices on farms were cleaning the facilities (67,70%) and disposal of animals (80,09%). It was observed that 60,18% of the farms apply some type of vaccine. It was also observed that worm was the biggest problem faced in sheep farms (97,80%), and 96,02% of the producers used vermifugation as the control method. Other health problems frequently reported by the interviewees were Myiasis (93,83%), Caseous Lymphadenitis (89,87%), Pododermatitis (87,67%) and Bronchopneumonia (81,94%). The results obtained in this work indicate that the BTV is present in the sheep herds of the states analyzed and that the exploitation of these in the Northeast has low technological level. It was also verified that the control of the diseases of these states is deficient, which explains, in part, the low productivity of the herds